Porovnání doby zasychání nátěrových hmot - Dolanová, Natálie; Natálie Dolanová (České vysoké učení technické v Praze, 2019)
Bakalářská práce se zaměřuje na rozbor obecných znalostí o nátěrových hmotách a informací spojených s touto problematikou. V praktické části jsou na vybraných nátěrových hmotách provedeny zkoušky zasychání a přilnavosti, které jsou následně v technicko- ekonomické části srovnány s cenou nátěru.

This thesis focuses on the analysis about paints and coating materials and information regarding this subject matter. In practical the part of the thesis, the drying and adhesion tests are made on selected coating materials. Results of these tests are then compared with the prices of each coating material in the technical-economic part of the thesis.
Comparison of drying time of paints
Keywords: Nátěrová hmota; zasychání; přilnavost; BK3; koroze; Paints; drying; adhesion; BK3; corrosion